Solid-state fermentation for phenolic compounds recovery from Mexican oregano (Lippia graveolens Kunth) residual leaves applying a lactic acid bacteria (Leuconostoc mesenteroides) - Bautista-Hernández, Israel (2024)
The Mexican oregano by-products are a source of bioactive molecules (polyphenols) that could be extracted using solid-state fermentation (SSF). This study fermented the by-products via SSF (120 h) with a lactic acid bacteria (LAB) Leuconostoc mesenteroides. Sequentially, a bioactive and chemical determination was made according to the phenolic content, antioxidant activity (DPPH●/FRAP), bioactive properties (α-amylase inhibition and antimicrobial activity against Escherichia coli), and chemical composition (HPLC-MS). The results showed that the total phenolics and flavonoid content, as well as the antioxidant activity, increased (0.60, 2.55, and 3.01 times, respectively) during the SSF process compared with unfermented material. Also, the extracts showed antimicrobial activity against E. coli and α-amylase inhibition. These inhibitory results could be attributed to bioactive compounds identified via HPLC, such as gardenin B, trachelogenin, ferulic acid, and resveratrol 3-O-glucoside. Therefore, the application of L. mesenteroides under SSF on oregano by-products comprises an eco-friendly strategy for their valorization as raw materials for the recovery of phenolic compounds that could be natural alternatives against synthetic antioxidant and antimicrobial agents, promoting a more circular and sustainable supply system within the oregano industry.